2010
DOI: 10.1002/jcp.22102
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 acts anti‐apoptotic and pro‐hypertrophic in adult cardiomyocytes

Abstract: Growth differentiation factor 15 (GDF15) is induced during heart failure development, and may influence different processes in cardiac remodeling. While its anti-apoptotic action under conditions of ischemia-reperfusion have been shown, it remained unclear if this is a broadly protective effect applicable to other apoptotic stimuli. Furthermore, effects on cardiac hypertrophy remained obscure. Therefore, we investigated the effects of GDF15 on induction of hypertrophy and apoptosis in ventricular cardiomyocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 27 publications
4
71
1
Order By: Relevance
“…In the present study, we found that GDF15 facilitated cancer stemness and radioresistance via activation of Smad1/5, as demonstrated in both cellular (Figure 6C-6F) and animal studies (Figure 7B-7D). Consistently, this Smad-associated pathway has been shown to be induced by GDF15 with anti-apoptotic effects in cardiomyocytes [58, 59]. Thus, GDF15 may have multiple functions in cells through distinctive signaling pathways depending on the specific tissue types.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, we found that GDF15 facilitated cancer stemness and radioresistance via activation of Smad1/5, as demonstrated in both cellular (Figure 6C-6F) and animal studies (Figure 7B-7D). Consistently, this Smad-associated pathway has been shown to be induced by GDF15 with anti-apoptotic effects in cardiomyocytes [58, 59]. Thus, GDF15 may have multiple functions in cells through distinctive signaling pathways depending on the specific tissue types.…”
Section: Discussionmentioning
confidence: 77%
“…GDF-15 was found to inhibit myocardial hypertrophy through a Smad2/3 pathway in a pressure-induced hypertrophy model (18), whereas directly treating cultured cardiomyocytes with GDF-15 results in pro-hypertrophic effect through a Smad1 pathway (19). It seems that the exact effect differs in different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that GDF-15 could play a role in the process of myocardial hypertrophy. So far, both pro-and anti-hypertrophic effects have been characterized (18,19); however, whether GDF-15 acts as an injury factor or a protector, as well as its precise function and mechanism of action, remains unclear.…”
mentioning
confidence: 99%
“…But how GDF-15 might interact with the different macrophage subsets during MI and HF needs clarification. GDF-15 was recently shown to have a direct action on cardiac myocytes themselves by promoting hypertrophic growth and acting anti apoptotic in cultured cardiac myocytes [52]. It remains currently unknown whether the increase in GDF-15 levels seen in HF is a protective mechanism of the body in response to injury or if such high GDF-15 levels might be detrimental and cause disease progression.…”
Section: Cytokines and Cardiac Outcomementioning
confidence: 99%